2018
DOI: 10.1016/j.bbadis.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine beta synthase-hydrogen sulfide system in paraventricular nucleus reduced high fatty diet induced obesity and insulin resistance by brain-adipose axis

Abstract: Hydrogen sulfide (H2S) is an essential neuromodulator, generates by cystathionine β synthase (CBS) or 3-mecaptopyruvate sulfurtransferase (3MST) in the brain. H2S can mediate paraventricular nucleus (PVN) neuron activity, and regulate neuroendocrine hormones secretion. On the other hand, CBS deficiency caused metabolic disorder and body weight reduction. However, whether CBS/H2S of PVN regulates neuroendocrine hormones to mediate energy metabolism is unknown. Here, we first identified the CBS co-localization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Hydrogen sulfide (H 2 S) is an essential neuromodulator in mammals (Zheng et al, 2018), which regulates numerous pathophysiological functions in the digestive, respiratory, circulatory and nervous systems (Kimura et al, 2012;Drapala et al, 2017;Yang et al, 2017;Yu et al, 2017;Zhou et al, 2018). Endogenous H 2 S levels have been detected in the brains of rats and humans (Wang, 2012;Yang and He, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is an essential neuromodulator in mammals (Zheng et al, 2018), which regulates numerous pathophysiological functions in the digestive, respiratory, circulatory and nervous systems (Kimura et al, 2012;Drapala et al, 2017;Yang et al, 2017;Yu et al, 2017;Zhou et al, 2018). Endogenous H 2 S levels have been detected in the brains of rats and humans (Wang, 2012;Yang and He, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CBS is an important enzyme to catalyze H 2 S [13]. Next, we found that high glucose reduced CBS protein levels in HT-22 cells ( Figure 2B, P < 0.001).The CBS level was obviously elevated in HG + SAMe and HG + NaHS groups compared with the HG group ( Figure 2B, both P < 0.001).…”
Section: Resultsmentioning
confidence: 77%
“…While, supplementation of H 2 S donor sodium hydrosul de (NaHS) protected hyperglycemiainduced myocardial tissue damage in vivo and in vitro [12]. In the central nervous system, the production of endogenous H 2 S is mainly catalyzed by cystathionine-β-synthase (CBS) [13]. Exogenous H 2 S inhibited the expression of pro-in ammatory factors and decreased the generation of oxidative indicator reactive oxygen species in the mouse model of Alzheimer's disease [14,15].…”
mentioning
confidence: 99%
“…The activation of mTORC1 signaling pathway is involved in the upregulation of CBS/H 2 S in pre-TRH level. Further results [74] indicated that leptin activated FOXO3a to increase CBS expression and H 2 S production in the hypothalamus, regulating neuroendocrine hormone (TRH and ACTH) to impact systemic glucose metabolism and energy homeostasis. However, the roles of H 2 S in regulating glucose metabolism control by the hypothalamus and its mechanism need to be further studied.…”
Section: H 2 S and Hypothalamusmentioning
confidence: 97%
“…CBS and 3-MST are the major endogenous enzymes in the brain that produce H 2 S [69] , [70] , [71] , [72] , [73] . CBS/H 2 S pathway in the hypothalamic paraventricular nucleus (PVN) was found to improve obesity and insulin sensitivity via the brain-adipose interaction [74] . CBS was detected in thyrotropin-releasing hormone (TRH) and CRH producing neurons.…”
Section: H 2 S and Hypothalamusmentioning
confidence: 99%